1999
DOI: 10.1111/1467-9493.00044
|View full text |Cite
|
Sign up to set email alerts
|

Malaria, Forests and People in Southeast Asia

Abstract: Forests and deforestation have important implications for health from ecological, social, economic and political points of view. These implications are examined for the case of malaria, a major public health problem which is difficult to control for various biomedical and entomological reasons. In addition, there are significant socio‐economic and political factors, particularly internal and international movements of population, which need to be examined for their role in the spread of malaria. Examples drawn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 5 publications
1
43
0
Order By: Relevance
“…14,[25][26][27][28][29] In Vietnam a large proportion of all malaria cases and deaths occurred in the central mountainous and forested areas. 28 In Myanmar, about 60% of the total malaria cases occurred in forest or forest fringe areas; forest workers (loggers, gem miners, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,[25][26][27][28][29] In Vietnam a large proportion of all malaria cases and deaths occurred in the central mountainous and forested areas. 28 In Myanmar, about 60% of the total malaria cases occurred in forest or forest fringe areas; forest workers (loggers, gem miners, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…In most parts of Southeast Asia, the year-round high rainfall and temperatures, and malaria vectors lead to persistent and intense malaria transmission. 25 However, in northern Myanmar the mountainous areas border with China, the high altitude leads to its difference from most parts of Southeast Asia; the hilly forested areas have low temperatures, fewer mosquito breeding sites, less malaria vector, and less parasite reservoirs caused by sparse population.…”
Section: Discussionmentioning
confidence: 99%
“…Provost (2011) reported that by 2010, countries with the highest death rate per 100,000 populations are Coted'lvoire with 86.15, Angola 56.93 and Burkina Faso 50.66 all in Africa. This is attributed to consistent temperature, high humidity, significant amount of rainfall, along with stagnant waters in which mosquitoes larvae readily mature, providing them with the environment they need for continuous breeding (Prothero, 1999) and thick vegetations which prevail in African countries. Greenwood et al (2005) state that majority of the cases were found in children less than five years old and pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…The year-round high rainfall and temperatures in tropical forests are ecological characteristics that favor the development of many kinds of mosquitoes that transmit pathogens that cause disease in humans 26 . Thus, the process of clearing forests and the subsequent human activities, such as agricultural and hydropower developments, have a high influence on the prevalence and incidence of diseases such as human malaria 27 .…”
Section: Discussionmentioning
confidence: 99%